Comparison of the effects of dexamethasone and ketorolac on edema and ecchymosis after rhinoplasty - Lotfi, Majid; Naghibzadeh, Bijan; khoshsirat, Shahrokh; Mohammadian, Yasaman; Peyvandi, Ali Asghar (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2022)
Background: Rhinoplasty is one of the most common plastic surgeries in the world. At the same time, rhinoplasty is considered one of the most precise, delicate and difficult plastic surgeries. Although this surgery is associated with some complications like any other surgery, because it is carried out to change the person's appearance and increase his/her satisfaction and self-confidence, attempts should be made to prevent the occurrence of complications as much as possible because edema and ecchymosis are considered as two consequences of rhinoplasty. Aim: Considering the severity of edema and ecchymosis after rhinoplasty and limited studies on the effect of non-steroidal compounds, therefore, the present study aims to compare the effect of dexamethasone and ketorolac severity on edema and ecchymosis after rhinoplasty in Loghman-e Hakim Hospital in 2021. Methods: This was a double-blind clinical trial that aims to compare the effect of dexamethasone and ketorolac on the severity of edema and ecchymosis after rhinoplasty among clients referring to the ENT clinic of Loghman-e Hakim Hospital during the year 2021. The study population included 81 patients applying for primary rhinoplasty were randomly divided into two groups using a randomized block design. Results: Although the mean edema and ecchymosis severity in the dexamethasone group was lower than the ketorolac group, the results of chi-square and independent t-test showed no significant difference between dexamethasone and ketorolac groups in terms of the severity of edema and ecchymosis. Therefore, both research hypotheses were rejected and the null hypothesis was confirmed. Conclusion: Despite the difference between the two groups in terms of severity of postoperative edema and ecchymosis, this difference was not statistically significant, which indicates the similar efficacy of the two drugs in reducing edema and ecchymosis after rhinoplasty.